Transcriptional Profiling of the Adult Hair Follicle Mesenchyme Reveals R-spondin as a Novel Regulator of Dermal Progenitor Function - Hagner, Andrew; Shin, Wisoo; Sinha, Sarthak; Alpaugh, Whitney; Workentine, Matthew; Abbasi, Sepideh; Rahmani, Waleed; Agabalyan, Natacha; Sharma, Nilesh; Sparks, Holly; Yoon, Jessica; Labit, Elodie; et al. (iScience, 2020)
The adult hair follicle (HF) undergoes successive regeneration driven by resident epithelial stem cells and neighboring mesenchyme. Recent work described the existence of HF dermal stem cells (hfDSCs), but the genetic regulation of hfDSCs and their daughter cell lineages in HF regeneration remains unknown. Here we prospectively isolate functionally distinct mesenchymal compartment in the HF (dermal cup [DC; includes hfDSCs] and dermal papilla) and define the transcriptional programs involved in hfDSC function and acquisition of divergent mesenchymal fates. From this, we demonstrate cross-compartment mesenchymal signaling within the HF niche, whereby DP-derived R-spondins act to stimulate proliferation of both hfDSCs and epithelial progenitors during HF regeneration. Our findings describe unique transcriptional programs that underlie the functional heterogeneity among specialized fibroblasts within the adult HF and identify a novel regulator of mesenchymal progenitor function during tissue regeneration. [Display omitted] •Transcriptional compartmentalization of the hair follicle mesenchyme•Hair follicle dermal stem cells (hfDSCs) exhibit a unique gene expression profile•DP-derived R-spondins coordinately activate hfDSCs and epithelial progenitors•Gene expression profiling of hair follicle dermal stem cells Biological Sciences; Developmental Biology; Stem Cells Research